2018
DOI: 10.1136/bmjopen-2018-023925
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study to explore the views of general practice staff on the use of point-of-care C reactive protein testing for the management of lower respiratory tract infections in routine general practice in England

Abstract: ObjectivesTo explore the knowledge, skills, attitudes and beliefs of general practice staff about C reactive protein (CRP) point-of-care tests (POCTs) in routine general practice and associated barriers and facilitators to implementing it to improve the management of acute cough.DesignA qualitative methodology including interviews and focus groups using the Com-B framework to understand individuals’ behaviour to implement CRP POCT in routine general practice. Data were analysed inductively and then aligned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 9 publications
1
59
0
1
Order By: Relevance
“…A qualitative study explored the views of general practice staff on the use of CRP POCT for the management of lower RTIs in England who felt the test could help general practice staff improve patient care and education if incorporated into routine care, but this would need enthusiasts with dedicated POCT instruments or smaller, cheaper, more portable instruments. 56 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study explored the views of general practice staff on the use of CRP POCT for the management of lower RTIs in England who felt the test could help general practice staff improve patient care and education if incorporated into routine care, but this would need enthusiasts with dedicated POCT instruments or smaller, cheaper, more portable instruments. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Barriers and facilitators to CRP POCT adoption A qualitative study explored the views of general practice staff on the use of CRP POCT for the management of lower RTIs in England who felt the test could help general practice staff improve patient care and education if incorporated into routine care, but this would need enthusiasts with dedicated POCT instruments or smaller, cheaper, more portable instruments. 56 A mathematical model for designing networks of CRP POCT could optimise the cost and travel distance for patients to access testing across a given region. 57 A mixed-methods UK study with CRP POCT confirmed costs and funding as important barriers in addition to physical and operational constraints and cited training and the value of a local champion as enablers.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…The stakeholders considered it not affordable or practical to deliver. While POC CRP testing is supported by examples of countries with low prescribing rates that routinely use it (e.g., Netherlands) and trial evidence showing it as an effective and safe strategy to reduce antibiotic prescribing for RTIs in general practice [14,35], it may not have sustained effects on prescribing behavior [36] and is often met with mixed views on its usefulness and feasibility from HCPs [37,38]. Moreover, 'co-organizing national AMS events for participants from different professional networks to facilitate multi-disciplinary AMS work' and 'promoting the use of patient records by pharmacists to review whether antibiotics were prescribed appropriately' seemed to be considered by stakeholders as unaffordable; 'providing information on opening hours of local healthcare services' (to reduce prescribing when concerned about limited access to healthcare) was considered unlikely to be effective; and 'providing training and resources to structure the ways of asking patients the right questions about self-limiting infections and identifying red flags to help decide what to advise patients' in community pharmacy was seen as of low relevance.…”
Section: Antibiotic Prescribing Data Monitoring and Feedbackmentioning
confidence: 99%
“…Similar to existing literature, both strategies were seen as ‘clinical tools’ to help manage clinical uncertainty, especially for those still developing clinical skills/experience: DPs were used to safety-net instead of re-consulting [ 27 , 28 , 36 ] and POC-CRPT to help assess illness severity and whether antibiotics are needed [ 23 , 24 , 29 , 30 , 35 , 37 39 ]. However, we found that clinical uncertainty about RTIs among experienced clinicians was seen as relatively ‘rare’.…”
Section: Discussionmentioning
confidence: 99%